The Effect of Temperature and Storage Time on the Quality of Frozen Food Nuggets (Journal of Chemical Process Engineering, 2025)
This study aims to determine the effect of storage temperature on the quality of nuggets (frozen food) and the effect of storage time on their quality.The test results showed that the Total Plate Count at room temperature (28ºC-30ºC) on day 1 did not meet the standard. Similarly, at refrigerator temperature (10ºC), the values on days 12 and 16 did not meet the standard. Meanwhile, at freezer temperature (-16ºC), all samples met the standard of